Corruption and the Extractive Industries Transparency Initiative. Issue 2 (1st February 2017) - Papyrakis, Elissaios; Rieger, Matthias; Gilberthorpe, Emma
Abstract: The Extractive Industries Transparency Initiative (EITI) has received much attention as a scheme that can help reduce corruption in mineral-rich developing economies. To our knowledge, this paper provides the first empirical attempt (using panel data) to explore how EITI membership links to changes in corruption levels. We also examine whether the different stages in EITI implementation (initial commitment, candidature, full compliance) influence the pace of changes in corruption. We find that EITI membership offers, on the whole, a shielding mechanism against the general tendency of mineral-rich countries to experience increases in corruption over time.